A phenomenological investigation into the psychoanalytic psychotherapist's experience of identifying, differentiating and processing the patient's transference-based and reality-oriented reactions - Danilewitz, Larry Mark (Rhodes University, Faculty of Humanities, Department of Psychology, 1993)
The aim of this study was to describe the psychoanalytically-oriented therapist's experience of identifying, differentiating and processing the patient's transference-based and reality-oriented reactions. In order to investigate the therapist's lived experience of being receptive to the total communication of the patient in the analytic situation, the researcher adopted the empirical phenomenological method. This descriptive and intuitive method grounded the researcher in the concreteness of the everyday life-world of the therapist, and enabled him to explicate the therapist's immediate, pre-theoretical experiences of his patient. The appropriate central research question, formulated to elicit the experience of this phenomenon, emerged through the process of enquiry during the pilot study. Thirteen experienced, psychoanalytically-oriented psychotherapists were interviewed and the five protocols considered most revelatory of the phenomenon under investigation were analyzed in detail. The remaining eight protocols were used to illuminate central themes and to clarify areas of uncertainty during the phase of formal explication. The central findings revealed that the oscillating process of the therapist as he shifts from being immersed in the world of his patient to being in a position of observation and self reflection is the fulcrum around which he evaluates the nature of his patient's communications. During this ongoing process of discrimination, living in duality, the therapist comes to experience himself as a patient scrutinized by his own and his patient's confrontations. His journey of disentanglement, the endeavour to differentiate his responses from his patient's actions, is dependent on his ability to engage in honest selfreflection and to access his pre-theoretical and articulated cognitions of his patient. This allows him to acknowledge his own role in what has unfolded interpersonally and to appropriate his previously denied feelings for and attitudes towards his patient, a prerequisite for the accurate and full appraisal of the nature of his patient's communications. Forsaking fixed judgements, the therapist becomes open to the confluence between the reality-oriented responses and transference-based reactions of his patient. This salient discovery, when dialogued with the literature, reinforced the theories of Greenson and Langs that not all the interactions between the patient and the analyst/therapist are transference-based and that it is therefore imperative that the analyst/therapist reflect on his participation in the analytic situation.
Keywords: Reality therapy; Transference (Psychology) -- Therapeutic use